Valorization of Brewer’s Spent Grain Using Biological Treatments and its Application in Feeds for European Seabass (Dicentrarchus labrax) - Fernandes, Helena; Salgado, José Manuel; Ferreira, Marta; Vršanská, Martina; Fernandes, Nélson; Castro, Carolina; Oliva-Teles, Aires; Peres, Helena; Belo, Isabel (Frontiers in Bioengineering and Biotechnology, 2022)
Brewer’s spent grain (BSG) is the main brewery industry by-product, with potential applications in the feed and food industries due to its carbohydrate composition. In addition, the lignocellulosic nature of BSG makes it an adequate substrate for carbohydrases production. In this work, solid-state fermentation (SSF) of BSG was performed with Aspergillus ibericus, a non-mycotoxin producer fungus with a high capacity to hydrolyze the lignocellulosic matrix of the agro-industrial by-products. SSF was performed at different scales to produce a crude extract rich in cellulase and xylanase. The potential of the crude extract was tested in two different applications: -(1) - the enzymatic hydrolysis of the fermented BSG and (2) - as a supplement in aquafeeds. SSF of BSG increased the protein content from 25% to 29% (w/w), while the fiber content was reduced to 43%, and cellulose and hemicellulose contents were markedly reduced to around 15%. The scale-up of SSF from 10 g of dry BSG in flasks to 50 g or 400 g in tray-type bioreactors increased 55% and 25% production of cellulase and xylanase, up to 323 and 1073 U g−1 BSG, respectively. The optimum temperature and pH of maximal activities were found to be 55°C and pH 4.4 for xylanase and 50°C and pH 3.9 for cellulase, cellulase being more thermostable than xylanase when exposed at temperatures from 45°C to 60°C. A Box–Behnken factorial design was applied to optimize the hydrolysis of the fermented BSG by crude extract. The crude extract load was a significant factor in sugars release, highlighting the role of hydrolytic enzymes, while the load of fermented BSG, and addition of a commercial β-glucosidase were responsible for the highest phenolic compounds and antioxidant activity release. The lyophilized crude extract (12,400 and 1050 U g−1 lyophilized extract of xylanase and cellulase, respectively) was also tested as an enzyme supplement in aquafeed for European seabass (Dicentrarchus labrax) juveniles. The dietary supplementation with the crude extract significantly improved feed and protein utilization. The processing of BSG using biological treatments, such as SSF with A. ibericus, led to the production of a nutritionally enriched BSG and a crude extract with highly efficient carbohydrases capable of hydrolyzing lignocellulosic substrates, such as BSG, and with the potential to be used as feed enzymes with remarkable results in improving feed utilization of an important aquaculture fish species.